Tectono‐morphological evolution of the Cauvery, Vaigai, and Thamirabarani River basins: Implications on timing, stratigraphic markers, relative roles of intrinsic and extrinsic factors, and transience of Southern Indian landscape. (17th June 2019) - Ramkumar, Muthuvairavasamy; Santosh, M.; Rahaman, Sheik Mohideen Abdul; Balasundareshwaran, Alankar; Balasubramani, Karuppusamy; Mathew, Manoj J.; Sautter, Benjamin; Siddiqui, Numair; Usha, Kumarasamy Parvathi; Sreerhishya, Kavungal; Prithiviraj, Govindaraj; Nagarajan, Ramasamy; et al.
Abstract : Peninsular India is an amalgam of transient landscapes evolved from the interactions between tectonic and climatic forcings. In order to appraise the tectono‐geomorphic evolution of South India, it is essential to understand the relationships between intrinsic and extrinsic processes and their geomorphic expressions at a river basin scale. Seven geomorphometric parameters, namely, longitudinal profile (Lp), asymmetry factor (Af), hypsometric curve and hypsometric integral (HI), mountain front sinuosity (Smf), river sinuosity (R), stream length gradient (Sl), and shape factor (Shp) were calculated for selected drainage basins of South India. Spatial analyses of these parameters in the light of systematic field mapping were attempted in this study. The results show the occurrences of southern sub‐basins with convex hypsometric curves indicating a youth stage and significant tectonic influence. The low and moderate Smf values within the basins are indicative of mountain fronts witnessing a high level of tectonic activity. The net effects of tectonic and geomorphometric processes are inferred to have been the responses of anti‐clockwise rotation of the Indian Plate and ridge uplift‐push from west. Directional change in Thamirabarani River Basin and drainage channel reorganizations in the Cauvery and Vaigai River basins stand testimony to these, among others. Amidst these, occurrences of tectonically quiescent regions and multiple incisions by river channels and flow of modern river channels in inherited palaeovalleys but on tangent directions of ancient flows are also observed. Five stages of landscape development are envisaged: First, inheritance of river basins from palaeodrainage systems; second, reversal of river flow directions during early part of Cenozoic and inception of evolution of modern river systems; third, during Miocene–Pliocene; fourth, during Pleistocene–Early Holocene; and fifth, during the Holocene–Anthropocene. The recent resurgence of tectonics is not only reflected in the shifting of axial rivers, but is also evidenced by seismicity and landslides/faulting. Together, transient nature of the Southern Indian Plate, first‐order control of tectonics, followed by climate and lithology over landscape evolution, inheritance of river valleys, synonymy of river basin responses to intrinsic and extrinsic geomorphic processes, however with unique signatures and basin‐scale responses, are inferred. Detailed morphometric studies and supplementation with precise age data may fine‐tune the proposed model. According to the model, inheritance of Mesozoic valley/structures during Late Jurassic–Early Cretaceous, drainage reversal and initiation of Cenozoic–Recent river basin evolution, intense peneplanation during Miocene–Pliocene, intense incision during Pleistocene, periodic climatic extremes during Early Cenozoic, Palaeocene–Eocene, Oligocene and corresponding pedogenesis, and terrace formation and sedimentation have been recognized. Based on the numerical ages and documentation of basin‐scale distribution of specific types of lithologies/weathering profiles/palaeosols, provisionally we recognize the laterite/ferricrete–bauxite–calcrete 53–50 and 37–23 Ma to be the oldest weathering profiles, palaeosols (I generation palaeosols) of alluvial fans with texturally immature parent rock clasts to be of 23–9 Ma, palaeosols with intensive calcitized rootlets that are found to occur in fluvial terraces of palaeo‐floodplain/natural levee (II generation palaeosols) to be of 3.5–2.5 Ma, and relict alluvium that are documented in inland river terraces and older deltaic plains and calcareous sandstones that are documented in coastal terraces to be of ~1 Ma old and attribute them to be the results of significant climatic events and Early Cenozoic uplift of Western Ghat that proceeded from south–north and its intensive tilt toward east since 25 Ma until today at a rate of 0.1 mm/year to be tectonic events that have significantly contributed toward landscape development on basin‐regional scales and concur with the evolutionary stages proposed in our model.